PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA YANG OVERTIME - Deviana, Nabila Tiara (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Increasing Human Rights Awareness is a form of worker protection from physical, technical and socio-economic protection provided by regulations governing the workplace. One of the problems that often occurs is overtime violations that are not in accordance with the provisions of Law No. 13 of 2003. One of the companies involved in the application of labor law protection is PT Hwaseung Indonesia. The purpose of writing this paper is to find out the legal protection for overtime workers at PT Hwaseung Indonesia. Based on the study, it is known that the Job Creation Law stipulates overtime work of 4 hours a day and 18 hours a week. Overtime hours are extended in accordance with the provisions of Article 78 of the Labor Code, Article 32/2003. According to this, overtime work is only allowed up to 3 hours in a day and up to 14 hours in a week. In this case, PT Hwaseung Indonesia, did not fully comply with the existing law as the company's maximum overtime is 20 hours.